Limit versus full creep for calves grazing late summer bluestem - B. Cochran; Gerry L. Kuhl; T. DelCurto; L. Corah; E. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1988)
Limit-feeding a soybean meal/milo creep supplement (1696 crude protein, average 3.096 salt) was compared with ad libitum consumption of the same supplement without salt or with no supplementation. Little difference was evident in average daily gain of calves among treatments. However, poor supplement consumption may have affected results.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Calves; Bluestem; Soybean/milo; Average daily gain